Micro-credit and good governance: models of poverty alleviation - Hossain, Ishtiaq (Brill Publishers, Leiden, Holland, 2000)
After decades of economic development, extreme poverty still persists in all societies. Too much wealth is concentrated in too few hands. This paper examines two models for economic development in a number of Asian countries.